Procedure-Related Access Site Pain Multimodal Management following Percutaneous Cardiac Intervention: A Randomized Control Trial - Liuda Brogiene; Aiste Urbonaite; Giedre Baksyte; Andrius Macas (Pain Research and Management)
Context. Approximately 1 in 20 patients undergoing the percutaneous cardiac intervention (PCI) experience severe procedure-related access-site (A-S) pain. The multimodal pain management model (MPM) can reduce the intensity and prevalence of pain and this approach was not investigated in the postprocedural pain management area. To address this, a randomized controlled trial was conducted in Hospital of Lithuanian University of Health Sciences Kauno klinikos in 2018. Methods. 137 patients who underwent PCI procedure via radial artery were randomly assigned (1 : 1) to the control (CG, n = 68) and intervention (IG, n = 65) groups. IG received MPM (paracetamol, ibuprofen, and the arm physiotherapy), CG received pain medication “as needed.” Outcomes were assessed immediately after, 2, 12, 24, and 48 h, 1 week, and 1 and 3 months after PCI. The primary outcome was A-S pain prevalence and pain intensity numeric rating scale (NRS) 0–10. Results. Results showed that A-S pain prevalence during the 3-month follow-up period was decreasing. Statistically significant difference between the groups (CG versus IG) was after 24 h (41.2% versus 18.5, p=0.005), 48 h (30.9% versus 1.5%, p≤0.001), 1 week (25% versus 10.8%, p=0.042), 1 month (23.5% versus 7.7%, p=0.017) after the procedure. The mean of the highest pain intensity was after 2 h (IG-2.17 ± 2.07; CG-3.53 ± 2.69) and the lowest 3 months (IG-0.02 ± 0.12; CG-0.09 ± 0.45) after the procedure. A-S pain intensity mean scores were statistically significantly higher in CG during the follow-up period (Wilks’ λ = 0.84 F (7,125) = 3.37, p=0.002). Conclusion. In conclusion, MPM approach can reduce A-S pain prevalence and pain intensity after PCI. More randomized control studies are needed.